Characterizing vibratory kinematics in children and adults with high-speed digital imaging - Patel, Rita; Dubrovskiy, Denis; Döllinger, Michael (Journal of Speech Language and Hearing Research, 2014)
PURPOSE The aim of this study is to quantify and identify characteristic vibratory motion in typically developing prepubertal children and young adults using high-speed digital imaging. METHOD The vibrations of the vocal folds were recorded from 27 children (ages 5-9 years) and 35 adults (ages 21-45 years), with high speed at 4,000 frames per second for sustained phonation. Kinematic features of amplitude periodicity, time periodicity, phase asymmetry, spatial symmetry, and glottal gap index were analyzed from the glottal area waveform across mean and standard deviation (i.e., intercycle variability) for each measure. RESULTS Children exhibited lower mean amplitude periodicity compared to men and women and lower time periodicity compared to men. Children and women exhibited greater variability in amplitude periodicity, time periodicity, phase asymmetry, and glottal gap index compared to men. Women had lower mean values of amplitude periodicity and time periodicity compared to men. CONCLUSION Children differed both spatially but more temporally in vocal fold motion, suggesting the need for the development of children-specific kinematic norms. Results suggest more uncontrolled vibratory motion in children, reflecting changes in the vocal fold layered structure and aero-acoustic source mechanisms.
EVALuna2:20185